Assembly processes of moss and lichen community with snow melting at the coastal region of the Barton Peninsula, maritime Antarctic. Issue 1 (December 2016) - Kim, Seok; Kim, Jun; Hong, Bo; Hong, Soon; Kim, Ji; Lee, Kyu
Abstract Background In this article, it was analyzed how snow melting affects the assembly of lichen and moss communities in a small area of the coastal region of Barton Peninsula, which is in maritime Antarctic. In the small area, even though there is a huge gap of difference of the environment between the snow-filled area and snow-melt one, the latter did not have distinctive environmental gradients. Results Depending on the snow melting time, coverage and species diversity of lichens and mosses tend to increase remarkably. For species with significant changes depending on the snow-covered period, there areAndreaea regularis, crustose lichens, Placopsis contortuplicata, Usnea aurantiaco -atra, and snow algae. In this area, the process of vegetation assembly process has shown the directional development in the order of snow algae→crustose, lichen sub-formation→fruticose lichen, moss cushion sub-formation (Andreaea sociation)→fruticose lichen, and moss cushion sub-formation (Usnea sociation), according to the order of snow melting. These directional development stages are shown in gradual change in small area with the snow melting phenomena. However, in the snow-free area, where water is sufficiently supplied, it is expected that moss carpet sub-formation (Sanionia sociation) will be developed. Vegetation development in the small area with the snow melting phenomena, depending on differences of resistance on snow kill and moisture settled by species in according to the time of snow melting, tolerance model to form community is followed. Conclusions The research results explain the development of vegetation in the Antarctic tundra and its spatial distribution according to the period for growth of lichens and mosses in the summer time by differences of snow melting in the small area. In the future, if research for the community development process in a large scale will be done, it will be helpful to figure out temporal and spatial dynamic of vegetation in the Antarctic tundra where snow and glaciers melt rapidly due to climatic warming.